PENYELAMATAN INFORMASI DOKUMEN/ARSIP DI ERA TEKNOLOGI DIGITAL - Sugiharto, Dhani (BACA: Jurnal Dokumentasi dan Informasi, 2010)
Documents/archives preservation in today’s modern perspective tends to lead to how the public can access information on documents/archives that is able to integrate technology in it. Long-term preservation is a primary goal of the documents/archives preservation program. When it saved in different media, both documents and archives already in the form of a digital format or are still analog, this preservation work can involve a continuous process in transferring content from old media to new media. Digitalization of documents/archives is one way process to change from conventional in various shades and shapes into an electronic document/archives.